2015
DOI: 10.4012/dmj.2014-197
|View full text |Cite
|
Sign up to set email alerts
|

Performance of dental impression materials: Benchmarking of materials and techniques by three-dimensional analysis

Abstract: Among other factors, the precision of dental impressions is an important and determining factor for the fit of dental restorations. The aim of this study was to examine the three-dimensional (3D) precision of gypsum dies made using a range of impression techniques and materials. Ten impressions of a steel canine were fabricated for each of the 24 material-method-combinations and poured with type 4 die stone. The dies were optically digitized, aligned to the CAD model of the steel canine, and 3D differences wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
0
11
0
6
Order By: Relevance
“…For some, the raw data was "cleaned" before creating the model surface [42]. Others used the RMS value for model differences, describing 66% of the difference values [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some, the raw data was "cleaned" before creating the model surface [42]. Others used the RMS value for model differences, describing 66% of the difference values [23].…”
Section: Discussionmentioning
confidence: 99%
“…Ender et al reported an in vitro precision of 14.3 µm for BC [35]. The higher deviations in the in vivo study are reflective of patient-relevant factors such as powdering, patient movement, and limited space [42]. In general, near-perfect scanning is necessary for all digital impression systems to attain optimal results [43].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Dental kliniklerde yaygın olarak kullanılan birçok elastomerik ölçü materyali vardır. 3,5 Bunlardan kondansasyon silikonları, ilave tip silikonlar ve polieterler en çok tercih edilen elastomerik ölçü maddeleridir. 3,[6][7][8] Elastomerik ölçü materyalleri, yüksek hassasiyet, üstün elastik geri dönme, minimum kalıcı deformasyon ve kabul edilebilir yırtılma mukavemeti gibi özelliklere sahiptirler.…”
Section: Gġrġġunclassified
“…10 Ayrıca bu cihazlar ile sadece belirlenen noktalar arasında ölçüm yapılabildiğinden çalışma modeli üzerinden üç boyutlu veriler toplanamaz. 5,10 Polimerizasyon süresince ve sonrasında, ölçü materyalleri boyutsal değişiklikler gösterdiğinden 2boyutlu ölçüm yöntemleriyle karmaşık değişimleri tespit etmek ve değerlendirmek zordur. 5,10,20 Bu nedenle farklı ölçü malzemelerinden yapılmış çalışma modellerinde meydana gelen boyutsal değişikliklerin tespit edilebilmesi için doğru ekipman ve ölçüm yöntemleri gereklidir.…”
Section: Gġrġġunclassified
See 1 more Smart Citation